Indeterminate dental pain: clinical characteristics and neurovascular compression; a retrospective case comparative study - Iwawaki, Kiyokazu; Watanabe, Motoko; Kimura, Yasuyuki; Maeda, Chizuko; Takao, Chihiro; Tominaga, Risa; Suga, Takayuki; Tu, Trang Thi Huyen; Nagamine, Takahiko; Toyofuku, Akira (Frontiers in Pain Research, 2025)
ObjectiveNon-odontogenic toothache, which is characterized by tooth pain without corresponding dental abnormality, is occasionally indeterminate due to its complicated persistent teeth, dentoalveolar and/or facial pain, specifically between patients with persistent idiopathic dentoalveolar pain (PIDAP) and those with trigeminal neuralgia (TN), accompanied by atypical sensations. This study aimed to clarify clinical characteristics in this patient population and to identify clinical real-world factors for differentiation.MethodsAll clinical data were retrospectively collected. Totally 340 patients, who were referred to our department with undiagnosed complicated persistent pain, were involved in the comparative analysis, depending on symptoms’ laterality, and 149 patients with unilateral symptoms were involved, depending on the presence of neurovascular compression (NVC) of trigeminal nerves and final diagnosis of PIDAP or TN.ResultsPatients with bilateral symptoms (n = 105) presented more severe affected pain sensations with higher pain catastrophizing compared to patients with unilateral symptoms (n = 234, p = 0.022). NVC was observed in 84 patients (56.4%); however, no significant difference in clinical features was observed depending on the presence of NVC. While patients with TN (n = 26) presented significantly stronger “shooting” and “stabbing” pain (p = 0.004, p = 0.006, respectively) with more severe NVC condition (p = 0.033), patients with PIDAP (n = 123) showed significantly higher scores in the central sensitization inventory (p < 0.001) and somatic symptom scales-8 (p = 0.004).ConclusionThese results suggest that relying solely on examining the presence of NVC is insufficient to distinguish PIDAP and TN in this patient population, but careful assessment of pain quality, pain catastrophizing, central sensitization, and somatic symptoms, besides detailed neurovascular conditions, is crucial.